2021
DOI: 10.3389/fcell.2020.592868
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors as Therapeutic Interventions on Cervical Cancer Induced by Human Papillomavirus

Abstract: The role of epigenetic modifications on the carcinogenesis process has received a lot of attention in the last years. Among those, histone acetylation is a process regulated by histone deacetylases (HDAC) and histone acetyltransferases (HAT), and it plays an important role in epigenetic regulation, allowing the control of the gene expression. HDAC inhibitors (HDACi) induce cancer cell cycle arrest, differentiation, and cell death and reduce angiogenesis and other cellular events. Human papillomaviruses (HPVs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 196 publications
(235 reference statements)
0
27
0
Order By: Relevance
“…In vitro and in vivo studies have demonstrated that HDAC inhibitors, such as the FDA approved drugs vorinostat, belinostat and panobinostat, could be a promising therapy for HPV-positive cancers [ 378 ]. A phase I/II study with the HDAC inhibitor entinostat is now recruiting patients with HPV associated malignancies (clinical trial study NCT04708470).…”
Section: Epigenetic Targeting Therapies For Treatment Of Virus-associated Tumorsmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that HDAC inhibitors, such as the FDA approved drugs vorinostat, belinostat and panobinostat, could be a promising therapy for HPV-positive cancers [ 378 ]. A phase I/II study with the HDAC inhibitor entinostat is now recruiting patients with HPV associated malignancies (clinical trial study NCT04708470).…”
Section: Epigenetic Targeting Therapies For Treatment Of Virus-associated Tumorsmentioning
confidence: 99%
“…Dietary polyphenols can modulate histone modification to prevent cancer by inhibiting HDAC [4,51]. Quercetin (inhibits HDAC2, HDAC4, HDAC7, and HDAC8), genistein (inhibits HDAC6 and tyrosine kinases), caffeic acid, and curcumin are the most well known for their capacity of inhibiting HDACs (Figure 6) [58]. Non-Coding RNA: MicroRNA MicroRNAs (miRNAs) are short, non-coding single-stranded RNA fragments that regulate cellular processes through transcriptional repression and degradation of messenger RNA (mRNA) [59].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Epigenetic altering factors include oncogenic viruses, such as high-risk human papillomaviruses (HR-HPVs), Epstein–Barr virus, Hepatitis viruses, and Kaposi’s sarcoma-associated herpesvirus [ 17 , 18 , 19 ]. These viruses have been found to be associated with epigenetic dysregulations in different tumors [ 20 , 21 , 22 ], whereas their oncoproteins have been shown to induce dysfunctions in proteins/enzymes involved in controlling DNA methylation, chromatin modification, and miRNA expression [ 17 , 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These viruses have been found to be associated with epigenetic dysregulations in different tumors [ 20 , 21 , 22 ], whereas their oncoproteins have been shown to induce dysfunctions in proteins/enzymes involved in controlling DNA methylation, chromatin modification, and miRNA expression [ 17 , 18 , 23 ]. Notably, epigenetic dysregulations have been shown to function as potential diagnostic and prognostic biomarkers as well as therapeutic targets in different virus-driven cancers [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%